Back from the Dead: Inside the Subhas Bose Mystery - Anju Dhar; DHAR (Anuj) (New Delhi Manas Publications, 2005)
Sixty long years have not been enough to end the Subhas Chandra Bose's death controversy. Behind the myths, lurks the dark realities. The intelligence think the matter is too volatile, and the media is forever chasing the leads. The judiciary has reasons to be suspicious.
Keywords: Bose, Subhas Chandra, 1897-1945 -- Death and burial; Nationalists -- India -- Biography; India -- Politics and government -- 1919-1947